THE IMAGE OF HORROR AS VIEWED IN EDGAR ALLAN POE'S THREE SHORT STORIES (LIGEA, THE BLACK CAT, THE FALL OF USERS) - Eko Djati Setiawati, Endang; Hersulastuti, Hersulastuti (Lire Journal (Journal of Linguistics and Literature), 2019)
Edgar Allan Poe is the father of horror stories. In his three short stories, Ligiea, the Fall of the house of Usher, The Black Cat, he portrays the image of horror in the form of being buried alive or premature burial, Mental Disorder or Madness or Mentally Ill, and Supernatural. Being buried alive can be seen in The Black Cat as well as in the Fall of the house of Usher. Mentally Ill can be found in the Black Cat and in the Fall of the house of Usher. Meanwhile Supernatural image of horror is reflected in Ligiea and in The Black Cat. Being buried alive is illustrated in the way when The Narrator of the Fall of the House help Roderick Usher entombed his twin sister, while in the Black Cat the Narrator buried his wife in the wall to conceal from the police investigation. Mental Illnesses can be seen in the Black Cat when the Narrator suffers from alcoholic addicted. Roderick Usher the character of The Fall of the house of Usher suffers from not only does he live in fear, but also to have lost all interest in every kind of social contact. Supernatural is portrayed in Ligeia, when the narrator’s wife, Ligiea, dead, she transforms into Lady Rowena, the new wife of the Narrator.